An enhanced synchronized multi-channel MAC scheme to improve throughput in VANET - C, Tripti; G, Jibukumar M (International Journal of Communication Networks and Information Security (IJCNIS), 2022)
The development of autonomous driving and intelligent transportation demands, fast, reliable and efficient data transmission for various applications in vehicular ad hoc network (VANET). This poses great challenges to the design of a media access control (MAC) protocol that can adapt to the frequent topological shifts. IEEE 1609.4 defines the multi-channel MAC layer implementation in VANET. The multi-channel operation works on a fixed synchronization interval that alternates between a control channel and service channels. The fixed interval leads to poor utilization of limited spectrum resources. In this paper, a multi-channel reliable MAC protocol (MCRMAC), that uses both the control channel and service channel irrespective of the interval to ensure proper and efficient throughput utilization in VANET is proposed. The simulations reveal the performance of the proposed scheme and it outperforms IEEE 1609.4 in terms of throughput.